2022
DOI: 10.1186/s12884-022-04945-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in the breastmilk of COVID-19 recovered women

Abstract: Objective Human milk contains antibodies against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which may serve as a protective factor through passive immunization in infants. The objective of this study was to measure the levels of anti-SARS-CoV-2 IgG and IgA in human milk and serum after a SARS-CoV-2 infection. Design Breast milk and serum samples from 72 lactating mothers with confirmed SARS-CoV-2 asymptomatic or symptomatic infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In comparison, the control group comprised 59,460 infants distributed as follows: 5832 (9.8%) hybrid immunity, 5430 (9.2%) natural immunity, 12,212 (20.5%) full vaccination, 21,287 (35.8%) partial vaccination, and 14,699 (24.7%) born to naïve mothers. Maternal post-partum vaccination could impact the risk of COVID-19 infection among infants 16 , 17 ; we therefore analyzed the frequency of post-partum vaccination among all subgroups and found similar rates (ranging from 7 to 10%). The distribution of the study population by maternal immunity status for case and control infants, over the study period, is illustrated in Supplementary fig.…”
Section: Resultsmentioning
confidence: 94%
“…In comparison, the control group comprised 59,460 infants distributed as follows: 5832 (9.8%) hybrid immunity, 5430 (9.2%) natural immunity, 12,212 (20.5%) full vaccination, 21,287 (35.8%) partial vaccination, and 14,699 (24.7%) born to naïve mothers. Maternal post-partum vaccination could impact the risk of COVID-19 infection among infants 16 , 17 ; we therefore analyzed the frequency of post-partum vaccination among all subgroups and found similar rates (ranging from 7 to 10%). The distribution of the study population by maternal immunity status for case and control infants, over the study period, is illustrated in Supplementary fig.…”
Section: Resultsmentioning
confidence: 94%
“…The difference might be due to the relatively small number of participants in our study. Other studies did not find an association between the antibody transfer to breastmilk and gestational age, but they were limited due to unsuccessful participation from all three trimesters [ 8 , 14 ]. We found the longest duration of positive serum IgG antibodies above the threshold to be 61.5 weeks from a women infected in her first trimester, and the duration may have been longer if the study had included a more extended follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Szcygiol and colleagues confirms the presence of SARS-CoV-2 IgA and IgG antibodies in the breastmilk of SARS-CoV-2--recovered women and found no relation of the antibody levels and the trimester of infection. The study, although including all three trimesters, does not elaborate on their specific findings in relation to the trimester of infection, and only collected breastmilk samples at one timepoint [ 7 , 8 , 9 ]. Based on the findings of Fich et al and the lack of representation of all three trimesters in the literature, we hypothesize that the timing of infection in naturally immunized mothers could have a possible impact on future SARS-CoV-2 maternal–neonate immunization.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies demonstrated that the probability of placental transmission is usually less than 5% [15] and that the virus cannot enter the mammary gland [16]; moreover, no live SARS-CoV-2 had been isolated in breastmilk, making it unlikely that breastmilk could be a vector for SARS-CoV-2 transmission [17,18]. Furthermore, other evidence showed the presence of SARS-CoV-2 IgA and IgG antibodies in the breastmilk of COVID-19 recovered women, raising the possibility that these antibodies could provide specific immunologic benefits to breastfeeding infants and provide protection against virus transmission [19,20].…”
Section: Discussionmentioning
confidence: 99%